2018
DOI: 10.1108/bjm-12-2017-0411
|View full text |Cite
|
Sign up to set email alerts
|

Association between strategic management accounting facets and organizational performance

Abstract: Purpose The purpose of this paper is to develop an extensive conceptualization of strategic management accounting (SMA) facets, as well as to explore the impact of these facets on both financial and non-financial measures of organizational performance (OP). Design/methodology/approach Data are collected from 435 accounting managers working in Saudi companies listed in the Saudi Stock Exchange. The study applies hierarchical regression analysis to test the association between SMA facets and OP. Findings The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 38 publications
(89 reference statements)
2
42
0
5
Order By: Relevance
“…Financial outcome is a basic element of performance in commercial organizations. Financial measures for such organizations include, for instance, sales and profit growth, market share, return on equity (ROE) and return on assets (ROA), cash flow (Alamri, 2019). Public organizations, including hospitals, should also act in a way that allows for the balancing of financial performance with broadly understood medical performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial outcome is a basic element of performance in commercial organizations. Financial measures for such organizations include, for instance, sales and profit growth, market share, return on equity (ROE) and return on assets (ROA), cash flow (Alamri, 2019). Public organizations, including hospitals, should also act in a way that allows for the balancing of financial performance with broadly understood medical performance.…”
Section: Methodsmentioning
confidence: 99%
“…Other non-financial measures that could be used to measure performance include innovative perfor-mance, employee satisfaction, new product offers (Alamri, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Prajogo (2016) found that a strategic fit between firm's strategies and business environment is important for achieving higher performance. Similarly, Alamri (2019) found that organizational performance depends much on the fit between strategic management accounting facets and organizational context. The results of these studies indicate the robustness of contingency theory in current literature.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
“…In the two main financial and non-financial quality categories, Alamri (2019) found thet the dimensions of strategy management accounting affected significantly the organization performance. Cadez and Guilding (2012) in their study that the effect on organizational efficiency of atrategic management accounting had a positive and varied influence and relied on different types of groups.…”
Section: H1 : Organizational Capabilities Have a Positive Influence Omentioning
confidence: 95%